Animal protection as a factor of ecosystem sustainability (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Species protection is considered a key component for maintaining and enhancing ecosystem resilience. This review synthesizes current understanding of mechanisms by which animals affect ecosystem functioning (trophic cascades, ecosystem-engineer species, pollination/seed dispersal, and biogeochemical cycles), integrates international guidance, and discusses practical approaches to population recovery and habitat connectivity. An empirical case of NABU-Kyrgyzstan is presented, illustrating contributions of rehabilitation, monitoring, anti-poaching and environmental education programs to the resilience of mountain ecosystems. The article provides practical recommendations for integrating species protection into landscape planning and sectoral policies.
Keywords: species protection; ecosystem resilience; biodiversity; rewilding